--- title: Homework 4 -- Optimization Methods author: Claudio Maggioni header-includes: - \usepackage{amsmath} - \usepackage{hyperref} - \usepackage[utf8]{inputenc} - \usepackage[margin=2.5cm]{geometry} - \usepackage[ruled,vlined]{algorithm2e} - \usepackage{float} - \floatplacement{figure}{H} - \hypersetup{colorlinks=true,linkcolor=blue} --- \maketitle # Exercise 1 ## Exercise 1.1 The lagrangian is the following: $$L(X,\lambda) = f(X) - \lambda \left(c(x) - 0\right) = -3x^2 + y^2 + 2x^2 + 2(x+y+z) - \lambda x^2 - \lambda y^2 -\lambda z^2 + \lambda =$$$$= (-3 -\lambda)x^2 + (1- \lambda)y^2 + (2-\lambda)z^2 + 2 (x+y+z) + \lambda$$ The KKT conditions are the following: First we have the condition on the partial derivatives of the Lagrangian w.r.t. $X$: $$\nabla_X L(X,\lambda) = \begin{bmatrix}(-3-\lambda)x^* + 1\\(1-\lambda)y^* + 1\\(2-\lambda)z^* + 1\end{bmatrix} = 0 \Leftrightarrow \begin{bmatrix}x^*\\y^*\\z^*\end{bmatrix} = \begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\-\frac{1}{2-\lambda}\end{bmatrix}$$ Then we have the conditions on the equality constraint: $$c(X) = {x^*}^2 + {y^*}^2 + {z^*}^2 - 1 = 0 \Leftrightarrow \|X^*\| = 1$$ $$\lambda^* c(X^*) = 0 \Leftarrow c(X^*) = 0 \text{ which is true if the above condition is true.}$$ Since we have no inequality constraints, we don't need to apply the KKT conditions realated to inequality constraints. ## Exercise 1.2 To find feasible solutions to the problem, we apply the KKT conditions. Since we have a way to derive $X^*$ from $\lambda^*$ thanks to the first KKT condition, we try to find the values of $\lambda$ that satisfies the second KKT condition: $$c(x) = \left( \frac{1}{3+\lambda} \right)^2 + \left( -\frac{1}{1-\lambda} \right)^2 + \left(-\frac{1}{2-\lambda}\right)^2 - 1 = \frac{1}{(3+\lambda)^2} + \frac{1}{(1-\lambda)^2} + \frac{1}{(2-\lambda)^2} - 1 =$$$$= \frac{(1-\lambda)^2(2-\lambda)^2 + (3+\lambda)^2(2-\lambda)^2 + (3+\lambda)^2 (1-\lambda)^2 - (3+\lambda)^2 (1-\lambda)^2 (2-\lambda)^2}{(3+\lambda)^2 (1-\lambda)^2 (2-\lambda)^2} = 0 \Leftrightarrow$$$$\Leftrightarrow (1-\lambda)^2(2-\lambda)^2 + (3+\lambda)^2(2-\lambda)^2 + (3+\lambda)^2 (1-\lambda)^2 - (3+\lambda)^2 (1-\lambda)^2 (2-\lambda)^2 = 0 \Leftrightarrow$$$$\Leftrightarrow (\lambda^4 - 6\lambda^3 + 13\lambda^2 - 12\lambda + 16) + (\lambda^4 + 2\lambda^3 - 11\lambda^2 - 12\lambda + 36) + (\lambda^4 + 4\lambda^3 - 2\lambda^2 - 12\lambda + 9)$$$$ + (-\lambda^5 -14\lambda^4 +12\lambda^3 +49\lambda^2 -84\lambda + 36) = $$$$ =-\lambda^5 +17\lambda^4 -12\lambda^3 -49\lambda^2 +48\lambda +13 = 0 \Leftrightarrow $$$$ \Leftrightarrow \lambda = \lambda_1 \approx -0.224 \lor \lambda = \lambda_2 \approx -1.892 \lor \lambda = \lambda_3 \approx 3.149 \lor \lambda = \lambda_4 \approx -4.035$$ We then compute $X$ from each solution and evaluate the objective each time: $$X = \begin{bmatrix}\frac1{3+\lambda}\\-\frac1{1-\lambda}\\ -\frac{1}{2-\lambda}\end{bmatrix} \Leftrightarrow$$$$\Leftrightarrow X = X_1 \approx \begin{bmatrix}0.360\\-0.817\\-0.450\end{bmatrix} \lor X = X_2 \approx \begin{bmatrix}0.902\\-0.346\\-0.257\end{bmatrix} \lor X = X_3 \approx \begin{bmatrix}0.163\\0.465\\0.870\end{bmatrix} \lor X = X_4 \approx \begin{bmatrix}-0.966\\-0.199\\-0.166\end{bmatrix}$$ $$f(X_1) = -1.1304 \;\; f(X_2) = -1.59219 \;\; f(X_3) = 4.64728 \;\; f(X_4) = -5.36549$$ ## Exercise 1.3 To find the optimal solution, we choose $(\lambda_4, X_4)$ since $f(X_4)$ is the smallest objective value out of all the feasible points. Therefore, the solution to the minimization problem is: $$X \approx \begin{bmatrix}-0.966\\-0.199\\-0.166\end{bmatrix}$$ # Exercise 2 ## Exercise 2.1 To reformulate the problem, we first rewrite the explicit values of $G$, $c$, $A$ and $b$: $$G = \begin{bmatrix}3&0&0\\2&2.5&0\\1&2&2\end{bmatrix}$$ $$c = \begin{bmatrix}-8\\-3\\-3\end{bmatrix}$$ $$A = \begin{bmatrix}1&0&1\\0&1&1\end{bmatrix}$$ $$b = \begin{bmatrix}3\\0\end{bmatrix}$$